High levels of physical activity are associated with lower levels of fatigue among lymphoma patients: Results from the longitudinal PROFILES registry. (May 2015) - Husson, Olga; Oerlemans, Simone; Mols, Floortje; Schep, Goof; Van De Poll-Franse, Lonneke V.
Abstract Background. Studies show a cross-sectional association between physical activity (PA) and fatigue among lymphoma cancer patients. However, few longitudinal studies have examined whether PA has a sustained effect on fatigue over time. Purpose. To examine the longitudinal relationship between PA and fatigue. Methods. All living individuals diagnosed with lymphoma between 1999 and 2010 as registered by the Dutch population-based Eindhoven Cancer Registry received a questionnaire on three time points. Generalized linear mixed models were used to estimate the independent effects of PA on fatigue. Results. PA and fatigue levels did not differ between patients short-term (< 1 year) and long-term after diagnosis (1–5 years or > 5 years). PA behavior was relatively constant over time with 84% of the patients meeting the Dutch PA guidelines at all assessment periods. Fatigue scores also remained fairly stable over time with 46% of the patients never being fatigued and 29% always being fatigued. Multivariate analyses showed that patients who met the PA guidelines scored 6.2 (95% CI 3.1–9.2) points lower on total fatigue over time (between subject effect; p < 0.01), compared to patients not meeting PA guidelines. Conclusion. During a period of two years, PA and fatigue levels were rather stable within lymphoma patients. Patients who met the PA guidelines reported lower levels of fatigue compared to those not meeting the guidelines, which appeared to be a constant association over time. The observed association between PA and fatigue underlines the importance to focus upon physical training in the care of cancer patients.